Kim Jong-Un’s Aims in Negotiating with Trump: Strategic or Tactical Flexibility? - Morteza Nourmohammadi, Ellias Aghili Dehnavi, Mohammad Alizadehjamal (International Journal of Advanced Science and Technology, 2020)
Washington has tried to persuade Pyongyang to disarm nuclear weapons with various measures and instruments. This situation led to a crisis of relations between the two countries after Trump’s victory in the election of the United States in 2016 and the rise of threatening verbal actions by the leaders of the two countries and numerous nuclear and missile tests by Pyongyang, to the extent that war could occur at any moment in the Korean Peninsula. But the United States and North Korea’s oral agreement in March 2018 for meeting and negotiating between two countries surprised everyone. In such a situation, the question which will be asked is that whether Pyongyang’s action is a tactical action aimed at reducing economic problems, or does Kim Jong-Un has decided to leave his nuclear program in exchange for financial, economic, and security assurances? The research findings indicates that North Korea is pursuing nuclear weapons because of confronting structural and regional developments that altered balance of power in the Korean peninsula. In other words, given North Korea’s deteriorated strategic environment and intensifying insecurity, nuclearization is not a rational option, but nuclear weapons are effective and efficient means to ensure North Korea’s security and survival. Kim Jong-un desire for negotiation is a tactical move to reduce economic, international and regional pressures to enhance nuclear capabilities and strengthen bargaining power in the future.